Reframing the climate debate: The origins and diffusion of net zero pledges. Issue 1 (21st November 2022) - Van Coppenolle, Hermine; Blondeel, Mathieu; Van de Graaf, Thijs
Abstract: Achieving net zero emissions has rapidly become the dominant long‐term objective guiding national climate policies. At the end of 2018, only 24 countries were considering or had adopted long‐term net zero targets. By the end of 2021, this had climbed to almost 150 countries, covering 89 per cent of global carbon emissions. In this article, we trace the origins and diffusion of net zero pledges through the lens of international norm theory. Drawing on a newly compiled database of national net zero targets, our analysis highlights the critical role played by climate scientists, transnational advocacy networks, and norm entrepreneurs in articulating the norm of net zero emissions. The IPCC's fifth assessment report was foundational, by introducing the concept of a cumulative carbon budget, allowing translation of abstract temperature goals into more actionable net zero targets. The norm of net zero has been institutionalised at the global political level in the period 2015–2018 and cascaded through the international system in 2019–2020. Yet, it remains subject to various forms of contestation, most notably regarding validity, fairness, scope, and implementation. The norm is now at a critical stage in its lifecycle that will decide whether it gets institutionalised or suffers backsliding and even erosion.